Pelatihan Pengelolaan Keuangan Bagi Pelaku UMKM Kelurahan Bendungan Hilir, Tanah Abang, Jakarta - Sunarmo, Sunarmo; Pardiansyah, Elif; Purwani, Anugerah Estri; Fattah, Iqbal; Pratiwi, Ramadhanty; Rahmi, Arneta (Universitas Nusantara PGRI Kediri, 2023)
The Covid-19 pandemic has an impact on the economic sector which causes people to suffer losses and even lose their livelihoods. One of the sectors affected is Micro and Small medium enterprises (MSMEs) in Bendungan Hilir. As is known that some communities of RW 04 Bendungan Hilir are MSMEs actors. The main problem of MSME actors during the pandemic is the lack of financial literacy knowledge, so the funds entering and exiting are not managed properly so that MSME actors do not have emergency funds or reserve funds. This community service aims to provide socialization and training on financial management for MSME actors. The methods used are direct surveys, questionnaires, socialization, and training. Based on the activity results, most MSME actors are beginning to understand the importance of financial management to anticipate the unexpected and for the betterment of their business.